Role of NG2 expressing cells in addiction: a new approach for an old problem - Somkuwar, Sucharita S.; Staples, Miranda C.; Galinato, Melissa H.; Fannon, McKenzie J.; Mandyam, Chitra D. (Frontiers in Pharmacology, 2014)
Neuron-glial antigen 2 (NG2) is a proteoglycan expressed predominantly in oligodendrocyte progenitor cells (OPCs). NG2-expressing OPCs (NG2-OPCs) are self-renewing cells that are widely distributed in the grey and white matter areas of the central nervous system. NG2-OPCs can mature into premyelinating oligodendrocytes and myelinating oligodendroglia which serve as the primary source of myelin in the brain. This review characterizes NG2-OPCs in brain structure and function, conceptualizes the role of NG2-OPCs in brain regions associated with negative reinforcement and relapse to drug seeking and discusses how NG2-OPCs are regulated by neuromodulators linked to motivational withdrawal. We hope to provide the readers with an overview of the role of NG2-OPCs in brain structure and function in the context of negative affect state in substance abuse disorders and to integrate our current understanding of the physiological significance of the NG2-OPCs in the adult brain.